Drawing at Visual Art’s teachers education: reflections from Designare (Revista Educação, Artes e Inclusão, 2020)
This work aims to present some reflections of my PHD research, with the title Designare: pontes artistico/educativas na formação docente em Artes Visuais. This research sought to build an interpretation about the Drawing and its teaching in the Visual Arts teachers education, questioning the "how to draw" and the "not knowing how to draw" in the view of the teachers who teach in this area at the university. At the methodological process, based the investigative ways in three research methodologies of Educational Research Based on Visual Arts (Viadel, 2005): Narrative, Autoetnography and A/r/tography and with research in specialized literature, problematization and justification in narrative memory and interviews making  with professors who teach Drawing in graduation courses in the area of Visual Arts at the University of Porto - UPORTO and at the Federal University of the Valley of São Francisco – UNIVASF. Focused on the understanding of the influence of drawing discourses and from drawings as visual narratives on teaching/learning of teachers practices in Visual Arts as rethinking historical issues in curricula, I analyzed issues of pedagogical practices of university professors and their repercussions on contemporary Visual Arts Teachers Education in Brazil and Portugal.
Keywords: artes visuais; desenho; educação artística